Effects of Biochar on Dispersibility of Colloids in Agricultural Soils. Issue 1 (1st January 2017) - Kumari, K. G. I. D.; Moldrup, Per; Paradelo, Marcos; Elsgaard, Lars; de Jonge, Lis W.
Abstract : The mobility of water‐dispersible colloids (WDCs) in soil may be influenced by soil management practices such as organic soil amendments. Biochar has recently been promoted as a useful soil amendment, and extensive research has been devoted to investigating its effects on soil macroscopic properties and functions. However, there is limited understanding of the effects of biochar application on micro‐scale particle dynamics. We conducted a field study to investigate the effects of the application of birch ( Betula spp.) wood biochar on colloid dispersibility with respect to application rate, history, and physicochemical soil properties. Undisturbed soil cores (100 cm 3 ) were collected from the topsoil of two agricultural sites in Denmark with soils of sandy loam texture. The two sites received biochar at different application rates (0–100 Mg ha −1 ) and were sampled 7 to 19 mo later. The WDC content was determined using an end‐over‐end shaking method on 100‐cm 3 intact soil cores, and the colloid solution was analyzed for electrical conductivity, pH, and zeta potential. The WDC content increased with biochar application rate because of biochar‐induced changes in soil chemistry and was strongly and positively correlated with the concentration of exchangeable monovalent cations in the soils. Biochar application increased pH and decreased electrical conductivity and zeta potential in the colloid suspension more in the short term (7 mo) than in the long term (19 mo). Thus, there is potential for biochar to induce short‐term changes in soil solution chemistry in agricultural soils, which may influence the mobility of soil colloids. Core Ideas: Biochar increased water‐dispersible colloid content in amended soils. WDC content was positively correlated with monovalent cations concentration in soil. Biochar aging prevented changes in soil chemical properties and WDC content.